SHRIMP DISEASE DETECTION USING BACK PROPAGATION NEURAL NETWORKS - P.VENKATESWARA RAO,; DR.A.RAMAMOHAN REDDY, (International Journal of Pharma and Bio Sciences, 2016)
There is a more expert knowledge in shrimp disease detection process. By considering the drawbacks of experts in identifying the disease for example, low level of knowledge and poor reasonableness, a new structure of shrimp disease recognition system that is based on neural networks is proposed. The recognition system uses the old cases of shrimp disease to make the network to learn and the white spot syndrome disease is recognized by the trained neural network. This technique helps us in finding of shrimp disease very quickly, and give another compelling strategy to the advancement of shrimp disease analysis framework.